The adventures of Robin Hood - Burrows, John, 1972-; Corvino, Lucy; Pyle, Howard, 1853-1911. (New York : Sterling Pub., 2005)
Recounts the legend of Robin Hood, who plundered the king's purse and poached his deer and whose generosity endeared him to the poor. Includes review questions.
4.8
3-6
3-6
Keywords: Robin Hood (Legendary character) -- Legends; Folklore -- England; Robin Hood (Legendary character) -- Legends; Folklore -- England; Robin Hood (Legendary character) -- Legends